Fructose overconsumption-induced reprogramming of microglia metabolism and function - Ting, Kenneth K. Y. (Frontiers in Immunology, 2024)
The overconsumption of dietary fructose has been proposed as a major culprit for the rise of many metabolic diseases in recent years, yet the relationship between a high fructose diet and neurological dysfunction remains to be explored. Although fructose metabolism mainly takes place in the liver and intestine, recent studies have shown that a hyperglycemic condition could induce fructose metabolism in the brain. Notably, microglia, which are tissue-resident macrophages (Mφs) that confer innate immunity in the brain, also express fructose transporters (GLUT5) and are capable of utilizing fructose as a carbon fuel. Together, these studies suggest the possibility that a high fructose diet can regulate the activation and inflammatory response of microglia by metabolic reprogramming, thereby altering the susceptibility of developing neurological dysfunction. In this review, we will summarize the recent advances in the understanding of microglia metabolism and how it supports its functions. We will then review the results from both in vivo and in vitro studies that have investigated the mechanistic link between fructose-induced metabolic reprogramming of microglia and its function. Finally, we will highlight areas of controversies and their associated implications, as well as directions that warrant future research.